Chem Piano Game to Increase Students Motivation and Retention of Learning Outcomes on the Periodic Table of Elements Material - Elok Najwa Salfiah; Achmad Lutfi (Jurnal Pijar MIPA, 2025)
The abstract nature of the Periodic Table of Elements necessitates interactive learning media to improve students’ motivation and learning outcomes. This study aims to determine the effectiveness of the Chem Piano game as a learning medium in enhancing students’ learning motivation, learning outcomes, and retention of learning outcomes related to the Periodic Table of Elements material. The research design employed was a pre-experimental approach using a One-Group pretest-posttest design. Data on students’ learning motivation were analyzed using a Likert scale consisting of positive and negative statements. Chem Piano was categorized as meeting the criteria for good learning motivation if it achieved a score of ≥ 69%. The learning outcome test data were analyzed using descriptive statistics to examine the mean and percentage of achievement, and the Wilcoxon Signed Ranks Test was used to determine the significance of the increase in learning outcomes. The results showed an increase in learning motivation, with a shift in category from low to very high. The Wilcoxon Signed Ranks Test for student learning outcomes yielded a significance value of 0.00 (< 0.05), indicating a statistically significant improvement between the pretest and posttest scores. Furthermore, the retention analysis yielded a very high retention value of 92.3%, indicating that students’ learning retention was stable. Based on the analysis and discussion, it can be concluded that the Chem Piano game is an effective learning medium for enhancing students’ motivation and learning outcomes in chemistry, particularly in relation to the Periodic Table of Elements. Therefore, it is recommended that this medium be used as an alternative instructional tool to enhance students’ motivation and learning outcomes, and that its implementation be further explored with a larger number of students.